Combination of GSIC and RIS-Enabled Signal Separation in IQ Domain for Parallel Reception with Imperfect CSI - Luo, Weiran; Huang, Xiaoxia (IEEE Vehicular Technology Conference, 2024)
Reconfigurable intelligent surfaces (RISs) can support concurrent transmissions through tailoring desired disparate channel conditions for multiple users. However, detection error probability of concurrent transmissions deteriorates as the channel gain becomes indistinguishable with growing number of users. Therefore, we investigate a practical group-level successive interference cancellation (GSIC)-based RIS-enabled multi-group parallel reception scheme in the presence of imperfect channel state information (CSI), in which GSIC is applied to distinguish user signals in different groups. In the same group, the signals from all users are tuned by RISs to form a higher-order meta-constellation to achieve parallel decoding. To maximize the sum throughput, the transmission power and phase shifts of RISs are jointly optimized subject to the detection error probability requirement. Particularly, transmission power is optimized with successive convex approximation (SCA) method, while a sequential optimization method is proposed for the design of the phase shift iteratively. Numerical results show that the sum throughput of the proposed algorithm increases by about 50% compared to hybrid GSIC and minimum mean square error (MMSE) scheme without RISs, and demonstrate the necessity of taking imperfect CSI into account.